Keanekaragaman, Kelimpahan Nisbi, Frekuensi dan Dominansi pada Nyamuk di Daerah Endemis Filariasis Kota Pekalongan Jawa Tengah - Ghofur, Abdul; Hadisaputro, Suharyo; Sayono, Sayono; Gumilar, Argo Ganda (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2024)
Latar belakang: Filariasis disebabkan cacing filaria dengan nyamuk sebagai vektor (vector borne disease). Kesepakatan global memberantas filariasis melalui The Global Goal of Elimination of Lymphatic Filariasis as a Public Health problem by The Year 2020 telah ditetapkan oleh WHO. Namun, sampai tahun 2021 masih terdapat 882 juta orang di 44 negara terancam filariasis, sehingga WHO menetapkan roadmap Neglected Tropical Diseases tahun 2021-2030. Indonesia memiliki 236 kabupaten atau kota endemis filariasis, pada akhir tahun 2021 tercatat 9.354 penderita. Kota Pekalongan salah satu daerah endemis filariasis. Nyamuk Culex sp. dan Aedes sp. ditetapkan sebagai vektor filariasis diperkotaan karena pernah ditemukan mikrofilaria pada spesies nyamuk tersebut, sehingga perlu penelitian parameter entomologi dan umur nyamuk untuk menemukan spesies yang paling berpotensi sebagai vektor filariasis.Tujuan: Mengetahui angka parameter entomologi untuk menentukan spesies yang paling berpotensi menjadi vektor di daerah endemis filariasis Kota PekalonganMetode: Penelitian observasional dengan rancangan crosssectional menggunakan metode purposive sampling. Sampel penelitian adalah nyamuk yang tertangkap di 6 rumah penderita. Penangkapan nyamuk selama 3 bulan. Hasil penelitian dianalisis secara deskriptifHasil: Jumlah nyamuk 1.160 ekor, dengan 5 jenis spesies yaitu Culex quinquefasciatus, Culex tritaeniorhynchus, Culex vishnui, Aedes aegypti, dan Anopheles vagus. Culex quinquefasciatus di Kelurahan Jenggot dan Medono mendominasi hasil perhitungan parameter entomologi dengan kelimpahan nisbi 70,01% dan 66.19%, frekuensi 1.0 dan 1.0, dominansi 70.01 dan 66.19 dan rata-rata umur 17 dan 19 hari.Simpulan: Tingginya angka parameter entomologi dan umur dari Culex quinquefasciatus menyebabkan Culex quinquefasciatus berpotensi menjadi vektor utama filariasis di Kota Pekalongan. ABSTRACTTitle: Diversity, Relative Abundance, Frequency, And Dominance Of Mosquitoes In Filariasis Endemic Areas Of Pekalongan District, Central JavaBackground: Filariasis is a vector-borne disease caused by filarial worms transmitted by mosquitoes. The World Health Organization (WHO) has established a global goal to eliminate filariasis as a public health problem by the year 2020, known as the Global Goal of Elimination of Lymphatic Filariasis. However, as of 2021, there are still 882 million people in 44 countries at risk of filariasis, prompting the WHO to develop a Neglected Tropical Diseases roadmap for 2021-2030. Indonesia, with 236 districts or cities endemic for filariasis, reported 9,354 cases by the end of 2021. Pekalongan City is one of the endemic areas for filariasis. Culex sp. mosquitoes and Aedes sp. mosquitoes are designated as filariasis vectors in urban areas due to the presence of microfilariae in these mosquito species. Therefore, it is essential to study the entomological parameters and age of mosquitoes to identify the species with the highest potential as a filariasis vector. Objective: This study aims to determine the entomological parameters and identify the species with the highest potential to become vectors in filariasis-endemic areas in Pekalongan City. Methods: This study utilized an observational research design with a cross-sectional approach, employing a purposive sampling method. The mosquito samples were collected from the homes of six individuals suffering from filariasis over a period of three months. Descriptive analysis was conducted to analyze the research findings. Results: A total of 1,160 mosquitoes were captured, consisting of five species: Culex quinquefasciatus, Culex tritaeniorhynchus, Culex vishnui, Anopheles vagus, and Aedes aegypti. Among these species, Culex quinquefasciatus in Jenggot and Medono Villages demonstrated dominance in the entomological parameter calculations, with a relative abundance of 70.01% and 66.19%, a frequency of 1.0 and 1.0, and a dominance of 70.01 and 66.19. The average age of these mosquitoes was 17 and 19 days, respectively. Conclusion: The high number of entomological parameters and the age of Culex quinquefasciatus mosquitoes indicate their potential as the primary vector for filariasis in Pekalongan City.